2016
DOI: 10.1093/rheumatology/kew212
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D treatment for connective tissue diseases: hope beyond the hype?

Abstract: The prevalence of vitamin D deficiency is increased among patients with CTDs. The active form of vitamin D (calcitriol) is a potent regulator of the immune system and may suppress inflammatory responses. This has led to claims that vitamin D may be a safe treatment, or a treatment adjunct, to reduce systemic inflammation in this patient population. It is important to note, however, that there is insufficient evidence from robust clinical trials to support these novel uses for vitamin D. In this review we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 93 publications
1
17
0
Order By: Relevance
“…The inclusion of healthy controls as comparator group is mandatory to rightly interpret data on vitamin D deficiency/insufficiency because of its broad diffusion and the high variability of its prevalence worldwide. Among 14 controlled studies reviewed by Reynolds and Bruce in 2017 [40], 12 of them showed significantly lower levels of serum vitamin D in SLE, while only two failed to detect different average values between cases and controls [11,41]. Hence, despite a prevailing consensus that SLE patients have significantly lower levels of vitamin D, variations in assay techniques, cut-off values, seasonality, ethnicity, age, sex, disease duration and latitude, all contribute to making the frequency of vitamin D deficiency/insufficiency challenging to compare between different studies.…”
Section: Prevalence Of Hypovitaminosis D In Diseasementioning
confidence: 99%
“…The inclusion of healthy controls as comparator group is mandatory to rightly interpret data on vitamin D deficiency/insufficiency because of its broad diffusion and the high variability of its prevalence worldwide. Among 14 controlled studies reviewed by Reynolds and Bruce in 2017 [40], 12 of them showed significantly lower levels of serum vitamin D in SLE, while only two failed to detect different average values between cases and controls [11,41]. Hence, despite a prevailing consensus that SLE patients have significantly lower levels of vitamin D, variations in assay techniques, cut-off values, seasonality, ethnicity, age, sex, disease duration and latitude, all contribute to making the frequency of vitamin D deficiency/insufficiency challenging to compare between different studies.…”
Section: Prevalence Of Hypovitaminosis D In Diseasementioning
confidence: 99%
“…Research has claimed that its dysregulation can lead to the development of numerous diseases, affecting the cardiovascular system, musculoskeletal system, and nervous system. [35][36][37][38][39] Optimal health benefits of exogenous and endogenous vitamin D might not be achieved without the adequate presence of magnesium, as the bioactivity of vitamin D is a magnesium-dependent process. 33,34 The purpose of this review article is to present the biological significance of magnesium in vitamin D metabolism and its therapeutic importance to minimize complications related to vitamin D deficiency.…”
mentioning
confidence: 99%
“…Vitamin D is a secosteroid hormone that contributes to calcium and phosphorus metabolism for healthy bone mineralization [12]. Vitamin D includes vitamin D 2 (derived from plants) and vitamin D 3 (derived from animals) as well as vitamin D metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, ~90% of vitamin D arises from endogenous synthesis by conversion of 7-dehydroxycholesterol into previtamin D by ultraviolet B radiations and then to vitamin D by a nonenzymatic transformation. Considering that vitamin D is biologically inactive, it is activated in a two-stage hydroxylation process: first, hepatic hydroxylation that results in 25-hydroxyvitamin D (25[OH]D) and, second, hydroxylation of 25(OH)D in the kidneys, resulting in 1,25-(OH) 2 D which is the active form of vitamin D [12, 14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation